A Cohort-Analysis of Age-Wealth Profile in Finland - Päivi Kankaanranta (Aboa Centre for Economics (ACE), 2019)
In this paper, the relationship between age and household net worth isexamined. The empirical analysis is based on a time-series of four cross-sections of the Finnish household wealth survey. Two different schemesare employed to identify age, cohort and time effects. Time-of-birth isfound to be an important determinant of asset accumulation. Con-trary to the life-cycle model, net worth increases even after retirementage. The cohort effect is found to follow a concave pattern instead ofincreasing monotonously. However, the accumulation behaviour bothover the life-cycle and across cohorts varies considerably by education.
Keywords: D15; E21; 330; wealth; life-cycle